Oxidative transformation of antiretroviral drug zidovudine during water treatment with permanganate: reaction kinetics and pathways - Kulkarni, Raviraj M.; Bhamare, Vijaykumar S.; Santhakumari, B. (Desalination and Water Treatment, 2016)
The presence of the pharmaceutical substances in the water has been reported by many studies and has attracted attention across the world. The mechanistic insight into oxidation of antiretroviral drug zidovudine (ZDV) by potassium permanganate was investigated between the pH values 3.0 and 9.0. The pH-dependent second-order rate constants were determined and rate constants decreased with an increase in pH. The products of the reaction were identified by high-resolution mass spectrometry. A probable mechanism is proposed which involves the formation of an intermediate complex between permanganate and ZDV, which further undergoes degradation in subsequent fast steps to form various oxidized products. The different parameters like effect of initially added products, solvent polarity, ionic strength, temperature, and pH on the rate of the oxidative degradation of ZDV by permanganate were systematically studied. The various activation parameters were determined from the effect of variation in temperature on the oxidative degradation of ZDV by permanganate in acidic medium and discussed in detail.
Keywords: Degradation; kinetics; Mechanism; Permanganate; Zidovudine